PENGARUH LIKUIDITAS, ROA,DAN SOLVABILITAS (LEVERAGE RATIO) TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Sonia, Siti; Praja, Yudha; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
Coal mining companies are a significant industrial subsector in Indonesia that have substantial impacts on the country and its society. It is believed that this sector plays a crucial role in transforming untapped natural resources into assets that can improve the quality of life by providing public facilities such as schools, housing, ports, roads, and others. The objective of this research is to determine the influence of Liquidity, ROA, and Solvability on Company Value through Dividend Policy. The sampling technique used in this study is Purposive Sampling. The population in this research comprises coal mining companies listed on the Indonesia Stock Exchange from 2019 to 2022. Data analysis and hypothesis testing in this study utilize Structural Equation Modeling – Partial Least Squares (PLS-SEM). The results of direct hypothesis testing using the Smart PLS 3.0 application indicate that Liquidity has a negative but insignificant effect on Dividend Policy. ROA has a significant positive effect on Dividend Policy, while Solvability has a positive but insignificant effect on Dividend Policy. Liquidity has a significant negative effect on Company Value, whereas ROA has a positive but insignificant effect on Company Value. Solvability has a significant positive effect on Company Value.Indirect hypothesis testing results show that Liquidity's impact on Company Value through Dividend Policy is positive but insignificant, ROA's impact on Company Value through Dividend Policy is negative but insignificant, and Solvability's impact on Company Value through Dividend Policy is negative but insignificant.